PESAN JURNALISME BENCANA DALAM FOTO: ANALISIS SEMIOTIKA ROLAND BARTHES PADA EVAKUASI KORBAN LIKUEFAKSI PALU 2018 - ardi ardi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
This study examines the journalistic message in Muhammad Fahrur Rasyid’s photograph of the evacuation of a victim during the 2018 Palu liquefaction disaster, employing Roland Barthes’ semiotic analysis. Photojournalism functions not merely as a factual record but also as a medium of social communication imbued with humanitarian meaning. The research data were collected through documentation and literature study, then analysed using Barthes’ three levels of signification: denotation, connotation, and myth. The findings reveal that at the denotative level the photo depicts the rescue process carried out by the SAR team; at the connotative level it symbolises vulnerability, hope, and solidarity; while at the myth level it represents a moral narrative of mutual aid as a universal humanitarian value. This research contributes to the study of disaster journalism by highlighting the humanistic and moral dimensions of a single photograph, shifting the focus away from mere representations of physical destruction or technical aspects of coverage. The study concludes that photojournalism can serve as a cultural text that fosters public empathy and collective memory of humanitarian tragedies.